Preparing to transition to secondary education: perceptions of Dutch pupils with migrant backgrounds. Issue 2 (3rd April 2018) - Rodrigues, Rosa G.; Meeuwisse, Marieke; Notten, Ton; Severiens, Sabine E.
Abstract: Background: The transition from primary school to secondary school is a crucial period of time for children and this may be especially the case for pupils with migrant backgrounds. While there has been considerable research on the transition from primary to secondary school, more needs to be known specifically about the experiences of this group of pupils during their final year of primary school, as they prepare for their transition to secondary school. Purpose: The study investigated how Dutch children with migrant backgrounds in their final year of primary school perceive the preparatory process for the transition to secondary school. In particular, we were interested in who the children felt were the important 'actors' (e.g. pupils, parents, teachers and others) in the preparatory process. Sample: We collected data from 76 primary school pupils from three schools in an urban city in the Netherlands. The sample included pupils who, according to the Dutch system, were preparing to follow an academic pathway (i.e. the tracks known in this system as 'HAVO' or 'VWO') and those who were preparing to follow a vocational pathway (i.e. the track known as 'VMBO') in secondary education. Design and methods: We used photo elicitation ( N  = 76) and also conducted semi-structured interviews with a subsample of the pupils ( N  = 25) to examine the roles of the important actors in the preparatory process. Data were analysed qualitatively; responses were coded and underwent pattern analysis in order to identify and describe repeating structures in the data. Data were grouped according to whether the pupils received school recommendations for an academic track or a vocational track. Results: Findings suggested that the pupils perceived the most important actors to be the pupil, the classroom teacher and the parents. Both teachers and parents were considered valuable resources for pupils in the preparatory process. Patterns representing the participants' perceptions of the roles of three actors – namely, (1) the child, (2) the classroom teacher and (3) the parents, were identified. Six patterns were identified with respect to the child, four with respect to the classroom teacher and two with respect to the parents. For some patterns, it was apparent that the responses of children in the vocational group and the academic group had different emphases. Conclusions: The study highlights the importance for teachers and parents of children in their final year of primary school to be aware of the pupils' perceptions of and feelings about their preparation for secondary school, so as to be in the best position to support them collaboratively.